INIBAP rapport annuel 2004 - International Network for the Improvement of Banana and Plantain (2005)
Reconciling modernity and tradition to conserve diversity ; when West Africa meets Latin America ; the accidental pathogen ; bringing back an old favourite, the capitalist way and INIBAP in brief.